Rethinking Noriko: marriage narrative as historical allegory in Ozu Yasujiro's The Moon Has Risen and other Occupation-era films. (15th September 2015) - Joo, Woojeong
Abstract : As a nonwestern filmmaker, Ozu Yasujiro has mostly been discussed in the context of his position in-between Japanese tradition and western modernity. This essay attempts to move beyond this dichotomy by analyzing Ozu's script for Tsuki wa nobori nu/The Moon Has Risen (1947), along with his other Occupation-era films, to consider the role of marriage narrative in allegorizing the historical context of the postwar Japan. While acknowledging the significance of the traditional elements in his Occupation-era films, this essay looks at the way tradition is linked to the reality of postwar Japan. Narratives about marriage, a ritual whose varying practices divide generations, presents a model of this imbricated historical consciousness through the interaction among characters with different spatial and temporal affinities. In The Moon Has Risen, a romantic relationship between two characters is constituted by a memory of the shared past, and with this memory in mind, the young generation initiates movement from Nara, a traditional city, to Tokyo, the place for life in the present. In this regard, the marriage narrative in Ozu's films becomes an allegorical vehicle that provides historical continuity from the wartime past to the present and future of the postwar Japan.